EXFOLIATIVE CHEILITIS (Case report) - I Wayan Arya K. Firdaus; Maharani Laillyza Apriasari (FKG Unlam, 2019)
Background : Exfoliative Cheilitis is defined as a chronic inflammatory disorder of the vermillion border of the lips, which is characterized by the persistent formation of scales and crusts. Underlying stress or psychiatric conditions may cause or exacerbate exfoliative cheilitis. Purpose : This paper reports the mechanisme of stress as the predisposing factor of exfoliative cheilitis. Case : The patient had been suffering the desquamation, dryness, and tenderness of lips for three months. The disease was not treated by any drugs. She consumed the multivitamin then ate more fruits and vegetables, but it was not getting well. Case Management : The anamnesis results that she had an allergy of some foods and never got serious diseases. There was story of biting and picking of lips, when she was getting stress. She was reffered by oral medicine specialist to get the complete blood count and Ig E test, but all of the results were normal. The final diagnosis was Exfoliative cheilitis, and the differential diagnosis was Allergic Stomatitis. She was prescibed triamcinolone acetonide 0,1% topically on her lips for three times until seven days. The instruction to patient were drinking much water and avoiding her habit of biting and picking of lips. Conclusion : Severe tress will trigger more proinflamation cytokines to increase epidermal growth factor (EGF) of oral mucous, so that caused unremitting desquamation.